How the social problems of a village are solved with the help of a theater: The case of the project “Theater is the heart of the revival of the village” - Mikhail N. Aleksashin (Управление культурой)
Based on the example of the project "Theater is the heart of the revival of the village", implemented in the village of Antonovka, in Tatarstan, the dynamics of the creation of the Center for the socio-cultural development of the village is described. The beginning of the project is downshifting by moving the capital's residents to the countryside, conflict with the local population, the search for a humanitarian way to solve the problems of families and the village as a whole. So the theater group was created. The main social problems in rural areas are the lack of cultural and leisure institutions, in general, cultural infrastructure, the experience of joint productive leisure of children, as well as institutionalized practices of cultural consumption, unemployment, poverty, low level of solidarity, generation gap, virtualization of everyday life. The purpose of the article is to characterize the socio-cultural changes in the village through the creation and development of an amateur theater. The article uses the case study method. Materials - documentary sources, chronological analysis, analysis of the effectiveness of fundraising, autoethnography. Problems of interaction with the local population, administration, within the team were solved. Since 2012, the initiative project has evolved from individual classes in stage movement to a theatrical production for schoolchildren, from children's theater to adult theater, from family and school performances to participation in festivals, performances at the cultural center. The creation of non-commercial organisation made it possible to participate in the competition for grants, and the level of competence in social design was raised. The result was the creation of the Center for Socio-Cultural Development. Today, there are 3 non-commercial organisations in the village, initiatives have been implemented to create a carpentry and pottery workshop, a craft art studio, a stable and a horse riding center. The Center for Socio-Cultural Design in the village of Antonovka performs resource functions. The economy of a non-commercial project consists of three sources: grant funds, personal contribution of the families participating in the project, and volunteer work. For 4 years, the amount of funds raised in the Center for Socio-Cultural Development of the Village amounted to about 3.9 million rubles. Participation in an amateur theater has all the signs of serious leisure: overcoming fears and difficulties, making efforts for a result, self-realization, etc. The result of the project was the formation of a creative environment - educational, shaping the personality of adults and children. The project had a positive impact on all spheres of life in the village - employment, productive leisure, the image of the territory, the creation of conditions for adaptation, the creation of families, etc. The amateur theater became a source of community formation.